Kenya : Ex Post Assessment of Longer-Term Program Engagement. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
This paper discusses key findings of the Ex Post Assessment (EPA) of Longer-Term Program Engagement paper for Kenya. This EPA focuses on 1993-2007, when Kenya was engaged in four successive IMF arrangements. Macroeconomic policy design was broadly appropriate, and implementation was generally sound. Growth slowed in the 1990s, but picked up after the 2002 elections, reflecting buoyant global conditions, structural reforms, and a surge of private capital inflows. Monetary policies were complicated by a reluctance to allow for full interest and exchange rate flexibility.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet